2016
DOI: 10.1186/s12891-016-0890-5
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with 3D isotropic high-resolution 3 T MR arthrography of the wrist

Abstract: BackgroundOur study was performed to evaluate the image quality of 3 T MR wrist arthrograms with attention to ulnar wrist structures, comparing image quality of isotropic 3D proton density fat suppressed turbo spin echo (PDFS TSE) sequence versus standard 2D 3 T sequences as well as comparison with 1.5 T MR arthrograms.MethodsEleven consecutive 3 T MR wrist arthrograms were performed and the following sequences evaluated: 3D isotropic PDFS, repetition time/echo time (TR/TE) 1400/28.3 ms, voxel size 0.35x0.35x0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Second, the qualitative assessment performed by visual evaluation and scoring of the ligaments may have been susceptible to inaccuracy because of the subjective perspective of the observers. A quantitative assessment by measuring relative signal intensity and relative contrast of the ligaments on digital images has been described, and could have been a more objective methodology. However, the clinical and practical utility of the individual imaging modality was questioned, and, as such, the qualitative assessment of the observers was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the qualitative assessment performed by visual evaluation and scoring of the ligaments may have been susceptible to inaccuracy because of the subjective perspective of the observers. A quantitative assessment by measuring relative signal intensity and relative contrast of the ligaments on digital images has been described, and could have been a more objective methodology. However, the clinical and practical utility of the individual imaging modality was questioned, and, as such, the qualitative assessment of the observers was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The thin contiguous sections with isotropic 3D MR imaging eliminate the partial volume averaging which occurs with 2D FSE imaging. 19 And finally, 3D MR imaging allows a decreased acquisition time as a function of obtaining a single isotropic 3D sequence versus three (axial, coronal, and sagittal) 2D sequences. 20 Yamabe et al 21 found that it took approximately 23 min to obtain imaging using a 2D sequence in three planes with and without fat suppression, while taking just 10 min to obtain equivalent isotropic 3D FSE images.…”
Section: Specific Techniques For 3t Imaging Of the Wristmentioning
confidence: 99%
“…Although several studies have compared the diagnostic performances of 3D isotropic sequences and 2D sequences in the wrist joints, most of these used a gradient-recalled echo sequence 8,23 or FSE images with intermediate-weighted sequences. 8,21,22 We used 3D isotropic T 1 weighted FSE sequences in this study, and to our knowledge, it was the first such study on the wrist joint. This sequence uses flip angle sweep, short and non-volume selective refocusing pulse, and parallel imaging, which makes it possible to get shorter echo spacing and a better signal-tonoise ratio.…”
Section: Patient Data and Results Are Summarized Inmentioning
confidence: 99%
“…10,[18][19][20] However, the number of studies that have used 3D isotropic FSE techniques in the wrist joint is limited. 8,21,22 Additionally, although the D-MRA 3D isotropic FSE sequence provides high contrast and spatial resolution, only one study to date has reported the diagnostic performance of 3D isotropic FSE D-MRA for the wrist joint. 21 However, they used 3D isotropic proton-density FSE MRI instead of T 1 weighted FSE MRI and did not use the arthroscopic findings Full paper: Diagnostic performance of wrist magnetic resonance (MR) arthrography BJR as the gold standard.…”
Section: Introductionmentioning
confidence: 99%